Albumin-to-Fibrinogen Ratio Independently Predicts 28-Day Mortality in Patients with Peritonitis-Induced Sepsis - Huiyu Tai; Zhiyun Zhu; Haifeng Mei; Wenbin Sun; Wei Zhang (Mediators of Inflammation)
Background. This study is aimed at investigating whether albumin-to-fibrinogen ratio (AFR) could independently predict the prognosis in patients with peritonitis-induced sepsis. Methods. A total of 246 eligible patients who were scheduled to undergo surgical treatment for peritonitis-induced sepsis were enrolled in this study. The primary observational endpoint was 28-day hospital mortality. Cox proportional hazards regression analysis with the Wald test was performed to identify prognostic factors for 28-day mortality in septic patients. Receiver operating characteristic (ROC) and Kaplan-Meier curve analyses were carried out to evaluate the association of baseline AFR and prognosis in septic patients. Results. Of all the cohort study participants, there were 59 nonsurvivors with a 28-day mortality of 24.0% (59/246). Baseline AFR (hazard ratio (HR): 0.67, 95% confidence interval (CI): 0.42–0.93, P=0.018) and the presence of septic shock (HR: 2.43, 95% CI: 1.42–3.91, P=0.021) were two independent prognostic factors for 28-day mortality in patients with peritonitis-induced sepsis by multivariate Cox analysis. Baseline AFR was a significant predictor for 28-day mortality with an area under the curve (AUC) of 0.751, a cut-off value of 8.85, a sensitivity of 66.10%, and a specificity of 70.05%, respectively (95% CI: 0.688–0.813, P<0.001). A low baseline AFR level (≤8.85) was significantly associated with a lower overall survival rate in septic patients by Kaplan-Meier curve analysis with log-rank test (P=0.004). Conclusions. This study indicates that AFR independently predicts 28-day mortality in patients with peritonitis-induced sepsis.